Metodología PBLE como guía del proceso de aprendizaje en Ingeniería. Primeros pasos en la UR - José Antonio Gómez Cristóbal; Joaquín Ordieres Meré; Manuel María Ruiz de Adana Santiago (Universidad de La Rioja, 2013)
This work presents some of the actions that a team of the Mechanical Engineering Department of the University of La Rioja develops as conceptual design specification of the formative method. It is a proposal of implantation, which will include a plan of communication and risks, to propose to the University users an alternative method in agreement with the European tendencies that go away in this sense during last years. The selected approximation for the proposal of implantation is based in the PBLE (Project Based Learning Engineering) methodology.